2018
DOI: 10.1159/000479167
|View full text |Cite
|
Sign up to set email alerts
|

Sensation of Cold during the Ice Water Test Corresponds to the Perception of Pain during Botulinum Toxin Bladder Wall Injections

Abstract: Aims: To investigate the association of bladder cold sensation (BCS) during the ice water test (IWT) and pain perception when botulinum toxin injections (BTI) are administered into the bladder wall. Material and Methods: In 86 patients with idiopathic overactive bladder, the BCS during the IWT was investigated. Patients were divided into 2 groups: with and without BCS. During subsequent administration of BTI, the number of perceived and painful injections as well as the pain levels on a 0-100 pain scale were c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Consequently, larger studies identifying which subgroups of patients tolerate the procedure most poorly would be valuable as these patients would benefit the most from the interventions identified in this review. Reitz et al 38 found a notable increase in bladder sensation and pain perception in patients who exhibited bladder cold sensation when tested with ice water instillation. Understanding which patients experience bladder cold sensation may allow the prediction of lower tolerability as well.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, larger studies identifying which subgroups of patients tolerate the procedure most poorly would be valuable as these patients would benefit the most from the interventions identified in this review. Reitz et al 38 found a notable increase in bladder sensation and pain perception in patients who exhibited bladder cold sensation when tested with ice water instillation. Understanding which patients experience bladder cold sensation may allow the prediction of lower tolerability as well.…”
Section: Discussionmentioning
confidence: 99%
“…This review identified three studies that identified that reducing the number of injections reduced pain scores. 20,21,26 The sample size was however small for all three studies (range [25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40]. Two of these studies also assessed whether fewer injections were associated with a reduction in effectiveness.…”
Section: Risk Of Biasmentioning
confidence: 99%